Facing Rose rosette virus: A risk to European rose cultivation. (3rd September 2020) - Vazquez‐Iglesias, Ines; Ochoa‐Corona, Francisco M.; Tang, Joe; Robinson, Rebekah; Clover, Gerard R. G.; Fox, Adrian; Boonham, Neil
Abstract: Roses ( Rosa ) are one of the most valuable ornamental flowering shrubs around the globe. They are susceptible to numerous pathogens that require management, increasing the cost of cultivation. Rose rosette virus (RRV; genus Emaravirus ) is a devastating virus that has been spreading since the 1940s in the United States and Canada. It is an emerging risk to European and worldwide rose cultivation, causing symptoms such as witches' broom, malformations, excessive thorn production, and eventually plant death. RRV is transmitted by the eriophyid mite Phyllocoptes fructiphilus and by grafting. Research is being undertaken to understand RRV and to find control measures and resistant cultivars, as they are not currently available. Early detection of the disease is the key to prevent the establishment and spread of RRV and its vector. Different molecular and serological diagnostic methods have been designed and implemented, including ELISA, RT‐PCR, RT‐qPCR, LAMP, and high‐throughput sequencing. RRV infected plants can remain symptomless for long periods, so these diagnostic assays are necessary in conjunction with visual assessment to facilitate early detection. Significant social, economic, and environmental impacts are expected if RRV and its vector establish and spread in Europe. Rose trade between countries is the most likely pathway of introduction of RRV into Europe. In this review we describe current knowledge about RRV, the molecular and serological methods available for the detection of this virus, pathways to entry, and the possible impact if it establishes and spreads in Europe. Abstract : In this review we describe current knowledge about Rose rosette virus, the molecular and serological methods available for its detection, pathways to entry, and the possible impact if it establishes and spreads in Europe.